(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the prevalence of common cardiovascular diseases among community-dwelling older adults in eight provinces/cities of Vietnam during 2021-2025. Methods: A multicenter cross-sectional study with comparative analyses was conducted on 6,203 older adults. Participants were selected using a multistage sampling approach. Cardiovascular diagnoses were standardized across study sites based on clinical assessment, electrocardiography, echocardiography, biochemical tests, and available medical records. Interviewers and physicians were centrally trained, and data were double-entered for quality assurance. Descriptive statistics and chi-square tests were used in the analyses. Results: The overall prevalence of cardiovascular diseases was 60.52%. Hypertension was the most common condition (46.59%), followed by cerebrovascular disease (9.40%), ischemic heart disease (9.06%), valvular heart disease (5.50%), heart failure (2.95%), arrhythmia (2.16%), and chronic lower-extremity venous disease (2.08%). The prevalence was 56.2% in those aged 60-69 years, 64.2% in those aged 70-79 years, and 63.1% in those aged 80 years or older (p < 0.001). The prevalence was 61.0% in men and 60.0% in women (p = 0.439). Among participants with cardiovascular diseases, 51.6% had concomitant hypertension. Conclusion: Cardiovascular diseases remain highly prevalent among older adults in the community. The burden is largely driven by hypertension and is higher in persons aged 70 years and older than in those aged 60-69 years, while sex differences are minimal.